A Comparative Study of Levamisole and Dexamethasone on the Chicks Immunity Which Inoculated with Newcastle Vaccine - Abdulla , A. Harith (International Journal of Poultry Science, 2014)
The objective of the study reported here was to evaluate the effects of Levamisole and dexamethasone on antibody titer in chicks against Newcastle vaccine.120 Fertile eggs at 18 days of incubation were divided into four equal group, 30 embryonated egg for each. The first group A inoculated with Levamisole that dose 0.1 mL/egg contain 1.25 mg active ingredient and live attenuated Newcastle vaccine(Lasota strain) in dose 0.1 mL/egg contain 4×108 Antigen in chick embryo at 18 days. The second group B injected with Dexamethasone that dose 0.1 mL/egg contain 0.2 mg/egg and Newcastle vaccine (Lasota strain) in dose 0.1 mL/egg contain 4×108 Antigen, in chick embryo at 18 days. The third group C treated with live attenuated Newcastle vaccine (Lasota strain) alone and saved as positive control in chick embryo at 18 days, whereas forth group D (negative control) injected with normal saline in dose 0.1 mL/egg at the same age and method of in group D. Result showed that slight effect of levamisol in increase Hatchability and livability ratio and it indicated sever effect of Dexamethasone in decreased Hatchability and livability. Heamagglutination inhibition test (HI) was used to evaluate the antibodies titer for all groups at 14 days of age. The above results showed the slight increase in HI titer for group A but it was not statisically significant as compared with group C, whereas result of group B showed significant decrease in HI titer as compared with group C.